2015
DOI: 10.2175/106143015x14362865226833
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination of Soil, Irrigation Water and Vegetables in Peri‐Urban Agricultural Areas and Markets of Delhi

Abstract: Dietary exposure to heavy metals, namely cadmium (Cd), lead (Pb), zinc (Zn), and copper (Cu), has been identified as a risk to human health through consumption of vegetable crops. The present study investigates heavy metal contamination in irrigation water, soil, and vegetables at four peri-urban and one wholesale site in Delhi, India, and estimates the health risk index. Most of the samples collected from peri-urban areas exceeded the safe limits of lead and cadmium, whereas only lead concentration was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…The results of this study showed greater mobility of Cd and Sb from soil to rice, followed by Mn, Pb, and As. The TF indicates a key process for human exposure to toxic heavy metals through the food chain [ 45 47 ]. Our results indicated that Cd and Sb contamination in soil poses a major human health risk.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed greater mobility of Cd and Sb from soil to rice, followed by Mn, Pb, and As. The TF indicates a key process for human exposure to toxic heavy metals through the food chain [ 45 47 ]. Our results indicated that Cd and Sb contamination in soil poses a major human health risk.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals accumulated in soils can cause adverse effects on the human body through direct routes, such as ingestion of soil, inhalation of dust particles and dermal absorption, 3 and indirect routes, such as the food chain. 4 Agricultural soil is the basis for the development of agricultural economy. It is of great signicance to study the contamination characteristics, source appointment and health risk assessment of heavy metals in agricultural soils.…”
Section: Introductionmentioning
confidence: 99%
“…This remains a problem, particularly in developing countries like Ethiopia where laws restricting exposure to wastewater do not exist. However, quite many research reports are available on the accumulation of heavy metals in soil and subsequent translocation and bioaccumulation by crops grown in wastewater irrigated soils [17,18]. Furthermore, gaps exist in evidencebased law-making measures committed to wastewater management in Ethiopia, which hinders attempts by the regulators and policy makers to influence common problems that occur at local and national levels through established rules and processes.…”
Section: Introductionmentioning
confidence: 99%